Antimycobacterial Activities of 2,4-Diamino-5-Deazapteridine Derivatives and Effects on Mycobacterial Dihydrofolate Reductase - Suling, William J. (American Society for Microbiology (ASM), 2000)
Development of new antimycobacterial agents for Mycobacterium avium complex (MAC) infections is important particularly for persons coinfected with human immunodeficiency virus. The objectives of this study were to evaluate the in vitro activity of 2,4-diamino-5-methyl-5-deazapteridines (DMDPs) against MAC and to assess their activities against MAC dihydrofolate reductase recombinant enzyme (rDHFR). Seventy-seven DMDP derivatives were evaluated initially for in vitro activity against one to three strains of MAC (NJ168, NJ211, and/or NJ3404). MICs were determined with 10-fold dilutions of drug and a colorimetric (Alamar Blue) microdilution broth assay. MAC rDHFR 50% inhibitory concentrations versus those of human rDHFR were also determined. Substitutions at position 5 of the pteridine moiety included [bond ]CH(3), [bond ]CH(2)CH(3), and [bond ]CH(2)OCH(3) groups. Additionally, different substituted and unsubstituted aryl groups were linked at position 6 through a two-atom bridge of either [bond ]CH(2)NH, [bond ]CH(2)N(CH(3)), [bond ]CH(2)CH(2), or [bond ]CH(2)S. All but 4 of the 77 derivatives were active against MAC NJ168 at concentrations of ≤13 μg/ml. Depending on the MAC strain used, 81 to 87% had MICs of ≤1.3 μg/ml. Twenty-one derivatives were >100-fold more active against MAC rDHFR than against human rDHFR. In general, selectivity was dependent on the composition of the two-atom bridge at position 6 and the attached aryl group with substitutions at the 2′ and 5′ positions on the phenyl ring. Using this assessment, a rational synthetic approach was implemented that resulted in a DMDP derivative that had significant intracellular activity against a MAC-infected Mono Mac 6 monocytic cell line. These results demonstrate that it is possible to synthesize pteridine derivatives that have selective activity against MAC.